10 years of the Urology Chair of the Siberian State Medical University. History of urology in Tomsk - Gudkov A.V. Gudkov A.V. Gudkov (Бюллетень сибирской медицины)
The paper describes the history of development of urology in Tomskand the Tomsk Region. After the foundation of the ImperialTomskUniversity, the first university behind the Ural Mountains, in 1878, urology began to develop at the Chair of Hospital Surgery. University professors E.G. Salishchev, P.I. Tikhov, N.I. Berezganovskii, N.A. Bogoraz, V.M. Mysh, A.G. Savinykh, V.M. Voskresenskii and others contributed a tremendous contribution to the development of urology. Since the course of urology was opened in 1959 by Prof. I.S. Petrov, the Clinic of the MedicalUniversitybecame an organizational-methodical center of the urological service of the Tomsk Region. The Clinic trained urologists for the municipal and regional health services. In 1976, and the independent course of urology was organized, and in 2002 the Urology Chair headed by Prof. A.V. Gudkov was founded.